Volumetric quantifications and dynamics of areas undergoing retrogressive thaw slumping in the Northern Hemisphere - Chunli Dai; Melissa K. Ward Jones; Jurjen van der Sluijs; Nina Nesterova; Ian M. Howat; Anna K. Liljedahl; Bretwood Higman; Jeffrey T. Freymueller; Steven V. Kokelj; Sindhura Sriram (Nature Communications)
Abstract Retrogressive thaw slumping (RTS) is a mass-wasting process characterized by upslope backwasting and rapid thawing of ice-rich permafrost. High-resolution digital elevation models (DEMs) from ArcticDEM enable the volumetric and soil organic carbon quantification of medium to large disturbance areas undergoing RTS ( ≥10,000 m2) for the Northern Hemisphere. Using DEM time-series analysis and deep learning, we retrieve a total of 2747 disturbance areas undergoing active RTS with a total volume loss of (317.0 ± 0.3) × 106 m3 between 2012 and 2022. Here we show that climatic drivers of RTS activity exhibit latitudinal and regional variations, specifically, the number of precipitation-driven RTS decreases linearly as latitudes increase, whereas temperature-driven RTS increases sharply. Finally, we estimate that 96% of detected RTS thawed ~1.95 × 10–3 Pg carbon per year, equivalent to ~0.2% of annual gradual thaw emission estimates. Our results highlight the complexity of regional RTS dynamics and the importance of high resolution, long-term monitoring efforts.